Amundsen Sea ice production and transport - Assmann, Karen M.; Hellmer, Hartmut H.; Jacobs, Stanley S. (Journal of Geophysical Research: Oceans, 2005)
Drift and variability of sea ice in the Amundsen Sea are investigated with ice buoys deployed in March 2000 and a coupled ice-ocean model. The Bremerhaven Regional Ice Ocean Simulations (BRIOS) model results are compared with in situ ocean, atmosphere, and sea ice measurements; satellite observations; and 8?19 months of buoy drift data. We identify a zone of coastal westward drift and a band of faster eastward drift, separated by a broad transition region characterized by variable ice motions. The model represents drift events at scales approaching its resolution but is limited at smaller scales and by deficiencies in the National Centers for Environmental Prediction forcing. Two thirds of the modeled ice production in the southern Amundsen moves westward near the coast, its transport modulated by meridional wind strength, damping sea ice formation in the eastern Ross Sea. Half of the ice exported from the Ross moves eastward into the northern Amundsen Sea, a net sea ice sink that also receives more than one third of the ice generated to its south. A low rate of exchange occurs with the Bellingshausen Sea, which must have a more independent ice regime. Snow ice formation resulting from high precipitation accounts for one quarter of the ice volume in the Amundsen Sea, aiding the formation of thick ice in a region with generally divergent ice drift. Freshwater extraction by sea ice formation is roughly balanced by precipitation and ice shelf melting, but a positive trend in the surface flux is consistent with an Amundsen source for reported freshening in the Ross Sea.
Publisher: John Wiley & Sons, Ltd
Keywords: Amundsenhavet; Rosshavet; Sørishavet; geofysikk; havis; oseanografi

Iron and mixing affect biological carbon uptake in SOIREE and EisenEx, two Southern Ocean iron fertilisation experiments - Bakker, Dorothee C.E.; Bozec, Yann; Nightingale, Philip D.; Goldson, Laura; Messias, Marie-José; de Baar, Hein J.W.; Liddicoat, Malcolm; Skjelvan, Ingunn; Strass, Volker; Watson, Andrew J. (Deep Sea Research Part I: Oceanographic Research Papers, 2005)
This study explores the changes in the surface water fugacity of carbon dioxide (fCO2) and biological carbon uptake in two Southern Ocean iron fertilisation experiments with different hydrographic regimes. The Southern Ocean Iron Release Experiment (SOIREE) experiment was carried out south of the Antarctic Polar Front (APF) at 61°S, 141°E in February 1999 in a stable hydrographic setting. The EisenEx experiment was conducted in a cyclonic eddy north of the APF at 48°S, 21°E in November 2000 and was characterised by a rapid succession of low to storm-force wind speeds and dynamic hydrographic conditions. The iron additions promoted algal blooms in both studies. They alleviated algal iron limitation during the 13-day SOIREE experiment and probably during the first 12 days of EisenEx. The fCO2 in surface water decreased at a constant rate of 3.8μatmday−1 from 4 to 5 days onwards in SOIREE. The fCO2 reduction was 35μatm after 13 days. The evolution of surface water fCO2 in the iron-enriched waters (or ‘patch’) displayed a saw tooth pattern in EisenEx, in response to algal carbon uptake in calm conditions and deep mixing and horizontal dispersion during storms. The maximum fCO2 reduction was 18–20μatm after 12 and 21 days with lower values in between. The iron-enriched waters in EisenEx absorbed four times more atmospheric CO2 than in SOIREE between 5 and 12 days, as a result of stronger winds. The total biological uptake of inorganic carbon across the patch was 1389ton C (±10%) in SOIREE and 1433ton C (±27%) in EisenEx after 12 days (1ton=106g). This similarity probably reflects the comparable size of the iron additions, as well as algal growth at a similar near-maximum growth rate in these regions. The findings imply that the different mixing regimes had less effect on the overall biological carbon uptake across the iron-enriched waters than suggested by the evolution of fCO2 in surface water.
Keywords: Sørishavet; alger; biogeokjemi; hydrografi; karbondioksid; marin kjemi; oseanografi

Bipolar patterns of intraspecific competition in bryozoans - Barnes, David K A; Kuklinski, Piotr (Marine Ecology Progress Series, 2005)
Polar shores probably represent the most dynamic and extremely disturbed environments on the globe. Nevertheless intense battles amongst sessile organisms for space are commonplace on hard substrata, mainly between fast-growing pioneer species. In this study we examined spatial interactions in encrusting species at 3 sites within each of 2 high Arctic localities, Horsundfjord (77°N) and Kongsfjord (79°N) in Spitsbergen, and 2 Antarctic localities, Signy Island (60°S) and Adelaide Island (68°S). In both polar regions 1 to 11% of encrusting fauna were involved in intraspecific interactions. Intraspecific competition was common; it usually involved just 1 or 2 pioneer species, mainly ended in tied outcomes, and most variability was at a local scale. The proportion of intraspecific encounters varied considerably at local (km) scales (19 to 99% intraspecific at different sites), reflecting an extremely patchy environment due to ice scour. Most intraspecific encounters resulted in ties (stand-offs) and again most variability was at a local scale. Many intraspecific encounters were constructive, forming large (>1 m3) foliaceous colonies (termed bioconstructions) whose 3D structures can harbour rich biotas. In other colonies intraspecific competition caused crowding and accelerated ovicell production (reproductive activity). Homosyndrome (fusion) was not observed in the Arctic and was rare in the Antarctic, where its frequency differed significantly between competitor identities. We found that the likelihood of meeting conspecifics versus other species and of tied outcomes in encounters was related to the performance of species in interspecific competition: ties were most common, and homosyndrome only occurred in poor competitors. In the context of rapid Arctic and west Antarctic warming and ice-loading of nearshore waters, we predict strongly changing patterns of intraspecific competition. Indeed we suggest that decreased patchiness of intra- versus interspecific competition and decreased levels of intraspecific competition should be strong indicators of increases in surface water ice-loading from ice-sheet collapses. KEYWORDS: Sublittoral · Benthos · Bioconstruction · Climate change · Homosyndrome
Keywords: Sørishavet; bentiske organismer; bryozoa; klimaendringer; marin biologi; miljøendringer; oseanografi; polarområdene

Pioneer whalers in the Ross Sea, 1923–33 - Barr, William; Watt, James P C (Polar Record, 2005)
On Christmas Eve 1923, the whaling factory ship Sir James Clark Ross, commanded by Captain Carl Anton Larsen and accompanied by five catchers, reached the front of the Ross Ice Shelf; these were the first whaling vessels to operate in the Ross Sea. They had been dispatched by the Norwegian whaling company Hvalfangeraktienselskapet Rosshavet, which had obtained a licence from the British government. For most of the 1923–24 season, Sir James Clark Ross occupied an uneasy anchorage in the deep waters of Discovery Inlet, a narrow embayment in the front of the Ross Ice Shelf, while her catchers pursued whales widely in the Ross Sea. During that first season they killed and processed 221 whales (211 blue whales and 10 fin whales), which yielded 17,300 barrels of oil. During the next decade, with the exception of the 1931–32 season, Sir James Clark Ross and two other factory ships operated by Rosshavet, C.A. Larsen and Sir James Clark Ross II, operated in the Ross Sea. From the 1926–27 season onwards these ships were joined by up to three other factory ships and their catchers, operated by other companies. During the decade 1923–33 the Rosshavet ships killed and processed 9122 whales in the Ross Sea sector, mainly in the open waters of the Ross Sea south of the pack-ice belt. Total harvest for all factory ships from the Ross Sea sector for the period was 18,238 whales (mainly blue whales) producing 1,490,948 barrels of oil. From 1924 onwards the Rosshavet catchers wintered in Paterson Inlet on Stewart Island, New Zealand, and from 1925 onwards a well-equipped shipyard, Kaipipi Shipyard, operated on Price Peninsula in Paterson Inlet to service the Rosshavet ships.
Publisher: Cambridge University Press
Keywords: Carl Anton Larsen; Rosshavet; Sørishavet; hvalfangere; hvalfangstselskaper; pelagisk

Cryosphere-hydrosphere interactions: Numerical modeling using the regional ocean Modeling System (ROMS) at different scales - Bergamasco, Andrea; Budgell, W. P.; Carniel, Sandro; Sclavo, Mauro (Il Nuovo cimento della Società Italiana di Fisica. C. Geophysics and space physics, 2005)
Conveyor belt circulation controls global climate through heat and water fluxes with atmosphere and from tropical to polar regions and vice versa. This circulation, commonly referred to as thermohaline circulation (THC), seems to have millennium time scale and nowadays-a non-glacial period-appears to be as rather stable. However, concern is raised by the buildup Of CO2 and other greenhouse gases in the atmosphere (IPCC, Third assessment report: Climate Change 2001, A contribution of working group I, II and III to the Third Assessment Report of the Intergovernmental Panel on Climate Change (Cambridge Univ. Press, UK) 2001, http://www.ipcc.ch) as these may affect the THC conveyor paths. Since it is widely recognized that dense-water formation sites act as primary sources in strengthening quasi-stable THC paths (Stommel H., Tellus, 13 (1961) 224), in order to simulate properly the consequences of such scenarios a better understanding of these oceanic processes is needed. To successfully model these processes, air-sea-ice-integrated modelling approaches are often required. Here we focus on two polar regions using the Regional Ocean Modeling System (ROMS). In the first region investigated, the North Atlantic-Arctic, where open-ocean deep convection and open-sea ice formation and dispersion under the intense air-sea interactions are the major engines, we use a new version of the coupled hydrodynamic-ice ROMS model. The second area belongs to the Antarctica region inside the Southern Ocean, where brine rejections during ice formation inside shelf seas origin dense water that, flowing along the continental slope, overflow becoming eventually abyssal waters. Results show how nowadays integrated-modelling tasks have become more and more feasible and effective; numerical simulations dealing with large computational domains or challenging different climate scenarios can be run on multi-processors platforms and on systems like LINUX clusters, made of the same hardware as PCs, and codes have been accordingly modified. This relevant numerical help coming from the computer science can now allow scientists to devote larger attention in the efforts of understanding the deep mechanisms of such complex processes.
Paper presented at: 8th Workshop on Calculation of High Performances in Italy, Milan, Italy. November 24-25, 2004.
Keywords: Sørishavet; geofysikk; klimaendringer; klimamodeller; oseanografi; polarområdene

On the taxonomic status of the Antarctic amphipod crustacean genera Eclysis (Astyridae) and Bathypanoploea (Stilipedidae), with partial redescription of their type species and description of Bathypanoploea polarsterni n. sp. - Berge, Jørgen; Vader, Wim (Organisms Diversity & Evolution, 2005)
The monotypic genus Eclysis K.H. Barnard, 1932 and its type species, E. similis Barnard, are redescribed based upon a newly discovered second specimen. The genus Bathypanoploea Schellenberg, 1939 is reviewed; B. schellenbergi Holman and Watling, 1983 is fixed as the type species. B. polarsterni n. sp. is described; Alexandrella pulchra Ren in Ren and Huang, 1991 is a new junior synonym of B. schellenbergi. The morphology of Eclysis and Bathypanoploea is examined, as well as their relationships to the Astyridae and Stilipedidae. See also Electronic Supplement at: http://www.senckenberg.de/odes/05-03.htm
Keywords: Sørishavet; amfipoder; taksonomi; zoologi

Hvalfangerselskapet Kosmos - Boye, Tore (Anders Jahres pengebinge, 2005)
Keywords: Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk

Southern Ocean deep-sea isopod species richness (Crustacea, Malacostraca): influences of depth, latitude and longitude - Brandt, Angelika; Ellingsen, Kari E.; Brix, Saskia; Brökeland, Wiebke; Malyutina, Marina (Polar Biology, 2005)
We examined deep-sea epibenthic sledge isopod data from the Atlantic sector of the Southern Ocean (SO) (depth range=742–5,191 m). Samples were taken during the expeditions EASIZ II (ANT XV-3) in 1998 and ANDEEP I and II (ANT XIX3/4) in 2002. A total of 471 isopod species were recorded from 28 sites. The species richness of the epibenthic sledge samples was highly variable (6–82 species). Species richness was highest at site 131-3 in 3,053 m depth in the north-eastern Weddell Sea. The highest numbers of species were sampled in the middle depth range and lower species richness was found in the shallower and deeper parts of the study area. Depth is suggested to explain isopod species richness better than both latitude and longitude. Between 58°S and 65°S, the number of species ranged from 9 to 82 (mean=35.9). Further south in the Weddell Sea, between 73°S and 74°S, species richness was lower and the number of species ranged from 6 to 35 (mean=19.2). With regard to longitude, the highest species richness (up to 82 species) was found between 50°W and 60°W in the area of the South Shetland Islands and around the Antarctic Peninsula, while numbers did not exceed 50 species in the eastern Weddell Sea. The haul length, ranging from 807 to 6,464 m, was positively correlated with depth; however, there was no linear relationship between haul length and species richness. We therefore suggest that depth was the most important factor explaining isopod species richness. However, only 28 sites were visited and the statistical power is thus limited. Sampling in the deep sea is expensive and time consuming and as yet this is the best isopod data set available from the Atlantic sector of the SO. Future expeditions are therefore important to better explain the current patterns of benthic diversity in Antarctica.
Keywords: Sør-Shetlandsøyene; Sørishavet; Weddellhavet; biodiversitet; isopoder; marin biologi

Polar bivalves are characterized by high antioxidant defences - Camus, Lionel; Gulliksen, Bjørn; Depledge, Michael H; Jones, Malcolm B (Polar Research, 2005)
Inevitably, aerobic life leads to the formation of deleterious reactive oxygen species (ROS) which participate in biomolecule oxidation, hence augmenting biomolecule turnover. Organisms have adapted to counteract the noxious effects of ROS by developing a battery of antioxidant defences (AOX) which comprise enzymes and low-molecular weight scavengers. Past studies have reported elevated AOX levels in polar pectinid bivalves compared with temperate congeners. This fi nding is controversial as mitochondrial ROS generation is low in polar versus temperate species, and, to date, there is no generally accepted explanation of the causes of increased basal AOX levels in polar waters. We suggest that the low food availability in those ecosystems may result in polar marine ectotherms diverting some energy into the maintenance of high AOX. We tested this hypothesis by comparing the total oxyradical scavenging capacity (peroxyl, hydroxyl and peroxynitrite) of three clam species: Laternula elliptica (Antarctic), Mya truncata (Arctic) and Mya arenaria (temperate). The data confi rmed that polar bivalves are characterized by higher AOX. Herein, we propose that high AOX is required in environments characterized by low food availability as AOX effi ciently protects biomolecules, notably the RNA expressed at high levels by cold-water ectotherms. Also, high AOX may explain the relatively long lifespan of most polar ectotherms.
Keywords: Sørishavet; marin biologi; muslinger; polarområdene

Økonomi og økologi i ishavene - Kjeldstadli, Knut (Et splittet samfunn : 1905-1935, 2005)
Keywords: Norge; Sørishavet; hvalfangst; pelagisk; økologi; økonomi

Telonema antarcticum sp. nov., a common marine phagotrophic flagellate - Klaveness, Dag; Shalchian-Tabrizi, Kamran; Thomsen, Helge Abildhauge; Eikrem, Wenche; Jakobsen, Kjetill S. (International Journal of Systematic and Evolutionary Microbiology, 2005)
Telonema is a widely distributed group of phagotrophic flagellates with two known members. In this study, the structural identity and molecular phylogeny of Telonema antarcticum was investigated and a valid description is proposed. Molecular phylogeny was studied using small-subunit rRNA (SSU rRNA) gene sequences. The pear-shaped cell had two subequal flagella that emerged laterally on the truncated antapical tail. One flagellum had tripartite hairs. The cell was naked, but had subsurface vesicles containing angular paracrystalline bodies of an unknown nature. A unique complex cytoskeletal structure, the subcortical lamina, was found to be an important functional and taxonomic feature of the genus. Telonema has an antero-ventral depression where food particles are ingested and then transferred to a conspicuous anterior food vacuole. The molecular phylogeny inferred from the SSU rRNA gene sequence suggested that Telonema represents an isolated and deep branch among the tubulocristate protists.
Publisher: Microbiology Society Type: Journal Article
Keywords: Sørishavet; Weddellhavet; fylogenetikk; marin biologi; mikrobiologi

Sediment characterization by echosounding and sampling - Kuhn, Gerhard; Brückner, Sylvia; Didik, Claudia; Forwick, Matthias; Hass, Christian; Lensch, Norbert; Schmitt, Wolfgang; Waldthausen, Constanze V; Wittling, Thomas (The Expedition ANTARKTIS-XX of RV Polarstern in 2002/2003 Reports of Legs 1 and 2, 2005)
The reconstruction of the paleoclimatic and paleoceanographic development of the late Quaternary Southern Ocean and adjacent continental areas in high temporal and spatial resolution is a main goal of our longterm study. During ANT-XX/2 the sedimentary budget of biogenic and terrigenous components and their variability was investigated in cooperation with geochemical projects. Main objectives were the relationships between production of biogenic components and input of terrigenous components and involved nutrients.
Keywords: Sørishavet; geokjemi; marin geologi; oseanografi; paleoklimatologi

Interplay of turbidite and contourite deposition along the Cosmonaut Sea/Enderby Land margin, East Antarctica - Kuvaas, Berit; Kristoffersen, Yngve; Guseva, J.; Leitchenkov, German; Gandjukhin, V.; Løvås, O.; Sand, Morten; Brekke, Harald (Marine Geology, 2005)
Multichannel seismic reflection data from the Cosmonaut Sea margin of East Antarctica have been interpreted in terms of depositional processes on the continental rise. A major sediment lens is present below the upper continental rise along the entire Cosmonaut Sea margin. The lens probably consists of sediments supplied from the shelf and slope, being constantly reworked by westward flowing bottom currents redepositing the sediments into a large-scale plastered drift deposit prior to the main glacigenic input along the margin. High-relief elongated and sometimes semicircular depositional structures are found on the upper continental rise, stratigraphically above the regional sediment lens, and were mainly deposited by the action of closely spaced turbidity currents. On the lower continental rise, large-scale sediment bodies extend perpendicular to the continental margin and were deposited as a result of down-slope turbidity transport and westward flowing bottom currents. The elongated sediment mounds on the upper and lower continental rise were deposited after initiation of glacigenic input to the slope and rise.
Keywords: Antarktis; Sørishavet; marin geofysikk; marin geologi

Holocene climate evolution in the high-latitude Southern Hemisphere simulated by a coupled atmosphere-sea ice-ocean-vegetation model - Renssen, Hans; Goosse, Hugues; Fichefet, Thierry; Masson-Delmotte, Valérie; Koç, Nalân (Holocene, 2005)
The Holocene climate is simulated in a 9000-yr-long transient experiment performed with the ECBilt-CLIO-VECODE coupled atmosphere-sea ice-ocean-vegetation model. This experiment is forced with annually varying orbital parameters and atmospheric concentrations of CO2 and CH4. The objective is to study the impact of these long-term forcings on the surface temperature evolution during different seasons in the high-latitude Southern Hemisphere. We find in summer a thermal optimum in the midHolocene (6-3 ka BP), with temperatures locally 3°C above the preindustrial mean. In autumn the temperatures experienced a long-term increase, particularly during the first few thousand years. The opposite trend was simulated for winter and spring, with a relatively warm Southern Ocean at 9 ka BP in winter (up to 3.5°C above the preindustrial mean) and a warm continent in spring (+3°C), followed by a gradual cooling towards the present. These long-term temperature trends can be explained by a combination of (1) a delayed response to orbital forcing, with temperatures lagging insolation by 1 to 2 months owing to the thermal inertia of the system, and (2) the long memory of the Southern Ocean. This long memory is related to the storage of the warm late winter-spring anomaly below the shallower summer mixed layer until next winter. Sea ice plays an important role as an amplifying factor through the ice-albedo and ice-insulation feedbacks. Our experiments can help to improve our understanding of the Holocene signal in proxies. For instance, the results suggest that, in contrast to recent propositions, teleconnections to the Northern Hemisphere appear not necessarily to explain the history of Southern Hemisphere temperature changes during the Holocene.
Keywords: Sørishavet; holocene; klimaendringer; klimamodeller; paleoklimatologi

”Admiralen” til Sydishavet – et 100 års minne - Ringstad, Jan Erik (Kulturminner, 2005)
Den 21. oktober 1905 forlot flytende kokeri Admiralen og hvalbåtene Ornen og Hauken Sandefjord med kurs for Falklandsayene og Syd Shetland. Dermed innledes et nytt kapittel i den moderne hvalfangsts histone. lnitiativtaker var Christen Christensen, hovedaksjoner og disponent for Aktieselskabet "Ørnen" som eide skipene det første norske hvalfangstselskap som uttrykkelig ble startet for eventuelt innkjøp av et dampskip for innredning til koker.
Keywords: Sørishavet; historie; hvalfangstselskaper; oppdagelsesreiser; pelagisk

Warming of the deep water in the Weddell Sea along the Greenwich meridian: 1977–2001 - Smedsrud, Lars H. (Deep Sea Research Part I: Oceanographic Research Papers, 2005)
The Weddell Deep Water (WDW) warmed substantially along the Greenwich meridian following the Weddell Polynya of the 1970s. Areas affected by the polynya contained ∼14GJ/m2 more heat in 2001 than in 1977. This warming would require a flux of ∼390W/m2 if it were to take place over a year. Large variations in heat content of the WDW are found between the Antarctic coast and Maud Rise (64°S). The small variation found north of Maud Rise is opposite in phase to that to the south, and the warming was close to monotonic south of 68°S. The mean warming of WDW along the section is ∼0.032°C per decade, comparable to the warming of the Antarctic Circumpolar Current. The mean warming compares with a surface heat flux of 4W/m2 over the 25 year period, an order of magnitude higher than the warming of the global ocean. As variation in mean salinity of the WDW follows the warming/cooling events, variation in inflow probably explains a cooling event between 1984 and 1989, and a warming event between 1989 and 1992. Cooling during the late 1990s is probably related to the reappearance of a polynya like feature in some winter months as an area 100km in diameter close to Maud Rise with 10–20% lower sea ice concentrations than the surrounding ocean.
Keywords: Sørishavet; Weddellhavet; havstrømmer; oseanografi; polynja

Dagbok fra en Sydhavstur 1906 - Sørlle, Petter; Kolltveit, Bård (Norsk sjøfartsmuseum. Årbok, 2005)
Publisher: Norsk sjøfartsmuseum Place: Oslo
Keywords: Sørishavet; dagbøker; hvalfangere; hvalfangstindustri; hvalindustri; hvalkokeri; polareksspedisjoner

Learning from the Antarctic whaling : report and proceedings - Walløe, Lars; Barthelmess, Klaus; Gambell, Ray; Ohsumi, Seiji; Komatsu, Masayuki (International Symposium Commemorating Centennial of the Antarctic Whaling, 2005)
Keywords: Antarktis; Sørishavet; historie; hvalfangstindustri; hvalindustri; pelagisk